A Ten-Year-Old Boy with Antiepileptic Drugs-Induced DRESS Syndrome - S. Vithana; M. H. A. D. De Silva; G. P. Hewawitharana (Case Reports in Pediatrics)
Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a life-threatening adverse drug reaction if it is not timely diagnosed and treated. This happens probably following a cascade of immune reactions after the administration of the drug ultimately leading to multiorgan failure and death. Several groups of drugs have been identified as potential aetiologies but the commonest one identified is antiepileptic drugs. The clinical features of DRESS syndrome usually appear several weeks after commencing the offending drug. Initially, fever lymphadenopathy and rash appear followed by hepatitis. Rash is the most prominent feature, and it is a generalized erythematous nonblanching maculopapular rash without the involvement of the mucus membranes or eyes. The rash desquamated over the following days and changed it’s context to an exfoliative dermatitis. We report a case of a 10-year-old boy who is one of the twins born to nonconsanguineous parents at 34 weeks of gestation.